Influencia de la motivación para mejorar el desempeño laboral del personal administrativo de la Municipalidad Distrital de Victor Larco Herrera - Maldonado Sánchez, Adaly Lizbeth (2017)
The present investigation was guided towards the analysis of the Influence of Motivation to improve the work performance of staff of the District Municipality of Victor Larco Herrera. To obtain information a survey on competency management and job performance 62 administrative workers between men and women was applied. The data were analyzed by means of statistical techniques as: charts of frequency and graphics. The research allows to conclude that motivation improves the work performance of the administrative staff, because the greater personal well-being, the greater yield and productivity will affect their work in the municipality. According to the evaluation carried out immediate bosses, employees of the municipality are productive, since is their environment pleasant and the municipality gives them the material and the appropriate infrastructure to carry out its functions in the best way, likewise gives the benefits to all employees.